FAKE NEWS E PROPAGANDA ELEITORAL NAS ELEIÇÕES DE 2022: O ENTENDIMENTO DO TSE - Mariz, Felipe Medeiros; Costa, Rodrigo Vieira (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
The use of social media for political propaganda since the 2016 US elections has increased the reach of fake news, making the delivery of this harmful content more widespread and personalized. In Brazil, the 2018 election was a turning point and led the Electoral Court to attempt to mitigate the damage caused by the circulation of defamatory and untrue content, especially on the internet. Among the various regulatory provisions, Resolution No. 23,610/2019 stands out, which regulates the forms in which electoral propaganda should occur, in addition to establishing the prohibited conduct for the 2022 election. Thus, this paper sought to understand what the Superior Electoral Court understands as fake news, and what means were used by the Electoral Court to curb the dissemination of false news. To this end, the rulings that addressed the topic in the year since the beginning of electoral propaganda in 2022 were analyzed. The methodology used in the work is qualitative and quantitative, with an analysis of the TSE's case law and a bibliographic review. Positions were identified requiring the removal of content whenever the electoral propaganda attributed crimes to the opposing candidate, or when their speeches were taken out of context, in addition to situations of narratives and speeches forged by artificial intelligence to try to deceive the citizen-recipient. Critical electoral propaganda and the broadcasting of old speeches by the candidate were also not prohibited by the Superior Electoral Court. The application of fines to disseminators of fake news varied according to the severity, period and duration in which they were broadcast. Therefore, the Court's conduct was to intervene only in situations of clearly false and/or misleading content, always determining short deadlines for the removal of the illicit content.